Compostos heteronucleares de dicetonatos de íons lantanídeos contendo unidades organometálicas: síntese, estudo teórico, propriedades estruturais e luminescentes - Moura, Jandeilson de Lima (2023)
The present work reports the synthesis, characterization and investigation of the photophysical properties of new Eu3+ ion diketonates complexes containing organometallic phosphinoxides as auxiliary ligands. Heterodinuclear compounds presented the general formulas [Ln(-dik)3(McBPO)], where Ln3+: Eu3+ or Gd3+, -dik means tta: 2-thenoyltrifluoroacetonate, btf: 3-benzoyl-1,1,1-trifluoroacetone, dbm: 2-dibenzoylmetanate, aind: 2-acetyl-1,3-indandionate or bind: 2-benzoyl-1,3-indandionate. McBPO represents FcBPO: 1,1'-bis(diphenylphosphoryl)ferrocene or RcBPO: 1,1'-bis(diphenylphosphoryl)rutenocene. The synthesized systems were characterized using the techniques of elemental microanalysis of C and H, absorption spectroscopy in the infrared region (FT-IR), absorption spectroscopy in the ultraviolet-visible region and diffuse reflectance. In addition to the aforementioned techniques, the organometallic ligands were further characterized by TG thermogravimetric analysis and mass spectrometry. Furthermore, the RcBPO ligand and the [Eu(aind)3(RcBPO)] complex were obtained in the form of crystals and had their structures obtained by the single crystal X-ray diffraction method and reported for the first time in the literature. The characterization results demonstrated unequivocally the formation of new heterodinuclear coordination compounds. The photoluminescent properties of Eu3+ complexes containing the McBPO ligand in the solid state were investigated from the excitation, emission and decay curves of the emitter state 5D0 lifetime, intrinsic and absolute quantum yields. The emission spectra of the compounds mainly show thin bands originating from intraconfigurational-4fN transitions, 5D0→7F0,1,2,3,4. Theoretical calculations were also performed to describe the spectroscopic properties of the investigated compounds. The JOYSpectra platform was used to obtain the theoretical Judd-Ofelt parameters of the compounds, which were calculated from the structures optimized at the DFT level. The electronic properties were described based on TD-DFT calculations at the ωB97X-D3/MWB52/Def2-SVP theory level. Furthermore, a rate equation model provided the theoretical absolute quantum yield, in excellent agreement with the experimentally measured data. Studies of luminescent properties have shown that Eu3+ complexes containing the RcBPO ligand exhibit high luminescence intensity in the red region, suggesting that these compounds constitute a new class of heterodinuclear systems with high potential for application as an emitting layer in light-converting molecular devices.